Analisis Faktor-Faktor Yang Memengaruhi Niat Penggunaan Aplikasi Smart Waste Management: Studi Kasus Aplikasi Duitin - Nugroho, Wahyudi Sri; Yekti Wirani; Yudho Giri Sucahyo (The Indonesian Journal of Computer Science, 2024)
In 2023, Indonesia produced 38 million tons of waste, 51% of which was household waste. One effort to address the waste problem is encouraging the public to sort recyclable waste (SDU) to reduce the amount of waste sent to landfills. The Duitin application is a mobile-based app that helps tackle waste issues through the collection of SDU sorted by households. This application is expected to play a significant role in supporting service operations. This study aims to analyze the factors influencing the intention to use the Duitin application. The model used in this research is adopted from the TAM, UTAUT, and ISSM frameworks. Previous studies were referenced to identify relevant variables, which were then incorporated into a questionnaire distributed through social media. Data analysis was conducted using the PLS-SEM technique on 244 respondent datasets. The results of the study revealed that two hypotheses were accepted, namely perceived usefulness and satisfaction, while four hypotheses were rejected: subjective norm, effort expectancy, social influence, and facilitating condition. This study serves as a reference for future research aimed at understanding factors influencing the adoption of smart waste management applications in the context of household recyclable waste in Indonesia.